Peasants as "Cosmopolitan Insurgents". (25th April 2022) - Ferrando, Tomaso; Mpofu, Elizabeth
Abstract : The lives of peasants are strongly interconnected with their territories, economies, and local institutions. At the same time, they have been historically defined by international processes and decisions that are taken elsewhere and affect their autonomy and identity. This is clearly the case when smallholders (that is, farmers who work small plots of land, mostly less than two hectares) are part of transnational food chains, but it is also true when their market is the local community: even when peasants do not grow global food commodities, they can be affected by the dynamics and continuous expansion of the transnational food system. Given the local impacts of international processes and regulatory frameworks, peasant organizations have increasingly organized translocally to participate in the international policy spaces, and try to subvert the legal structures that are shaping their lives and territories. This essay discusses those attempts by peasants to organize beyond their local realities to increase their political power and promote their vision of international economic law as a central piece in their long term strategy for recognition, food sovereignty, and consolidation of territorial and agroecological food systems. The essay provides a diagnosis of farmers' silencing and exclusion by international economic law, presents the movement La Vía Campesina as a platform for translocal solidarity and multi-scalar engagement, and elaborates on peasants' "cosmopolitan insurgence" and their promotion of food sovereignty as an alternative project for international economic law.